Impact of regular online MCQ practice on academic performance of first-year Vietnamese students in Biology-Genetics: A cross-sectional study in MeKong Delta - Cao, Nguyen Thi Tai (E-learning and digital media, 2025)
Background: Regular assessments play an important role in final course grades, accounting for 30% of the score, and can also help students achieve higher marks in the final exams. Students’ regular participation in online tests may reflect their self-study skills and time management abilities to achieve high scores in final exams. Objectives: This study aims to identify certain characteristics of students through their engagement in online regular tests in Biology-Genetics and to determine whether the frequency of studying on the online MCQ system affects their final exam results. Subjects and methods: A total data of 413 students who completed the final exam for this subject and participated in online regular tests during the first semester of the 2024-2025 academic year were analyzed. Statistical analyses were conducted using R, including descriptive statistics, Pearson’s Chi-squared test, Fisher’s exact test, Kruskal-Wallis rank sum test, and multivariable linear regression, with a significance level of p < 0.05. Conclusion: The study confirms the importance of completing online MCQ tests for students’ academic performance. Analysis using the Kruskal-Wallis rank sum test shows that higher frequency in completing tests is associated with better final exam scores ( p < 0.05). Moreover, the diligence of students in Traditional Medicine significantly contributes to higher final exam scores. Multivariable linear regression analysis explains 52.01% of the variation in students’ final exam scores. It indicates that the number of test attempts can improve average exam scores, with each attempt on Topic 5 increasing the average score by 0.12 points ( p < 0.05). Additionally, factors such as major, gender, course, and ethnicity also play important roles in explaining differences in academic performance. Understanding these factors will help educators design and implement more effective teaching and assessment methods to support student learning and improve their academic outcomes.